Relação entre gordura corporal, número de passos e capacidade cardiorrespiratória de mulheres na pós-menopausa - Rossi, Fabrício E. [UNESP]; Buonani, Camila [UNESP]; Rosa, Clara S. C. [UNESP]; Diniz, Tiego A. [UNESP]; Christofaro, Diego G. D. [UNESP]; Freitas, Ismael F. [UNESP] (My University, 2014)
Model of the study: Cross-sectional study. Objective: To verify the relationship between body fat, number of steps and cardiorespiratory fitness in postmenopausal women.Methods: 57 women over 50 years were divided into four groups according to the median of age (<60.8 and = 60.8 years) and median of body fat (<22.8 =33.2 Kg). The dual-energy X-ray absorptiometry (DXA) was used to estimate total fat mass, percentage of body fat and trunk fat. The test of six-minute walk was used to analyze the cardiorespiratory fitness and a tri-axial accelerometer to determinate the number of steps per day. Results: Younger women accumulated more steps per day (<60.8= 7727.5 x =60.8= 6173.2, p <0.014) and among the younger women group, the one with lower body fat accumulated more steps/day (lower fat = 8405 steps x higher fat= 6118 steps, p <0.031). There was no significant difference between women with higher age and higher body fat. Regarding to the cardiorespiratory fitness, there was no significant difference between the groups. All variables of body fat presented low and negative relationship with both number of steps in the younger group and cardiorespiratory fitness in older age group.Conclusion: Body fat present low and negative correlation with the number of steps and cardiorespiratory fitness in postmenopausal women, furthermore, the age seems to influence this relationship.
Relationship between body fat, number of steps and cardiorespiratory fitness in postmenopausal women